A prospective observational study of drug therapy problems in medical ward of a referral hospital in northeast Ethiopia - Yaschilal Muche Belayneh; Gedefaye Amberbir; Asrat Agalu (BMC, 2018)
Abstract Background Drug therapy problem is any undesirable event experienced by a patient during drug therapy that interferes with achieving the desired goals of therapy. Drug therapy problems are common causes of patient morbidity and mortality. There was no study that has been done on drug therapy problems in the study area, Dessie referral hospital, northeast Ethiopia. Method A prospective observational study was conducted among hospitalized patients in the medical ward of Dessie referral hospital from March 01 to May 31, 2014. Ethical approval was obtained and informed consent was signed by each study participant before the commencement of the study. All patients admitted to the ward during the study period were included in the study. Data regarding each patient's demographics, medical condition, drug therapy and patient compliance to the drug therapy were collected using pretested checklists, and drug therapy problems were determined based on the standard practice and textbooks. Descriptive statistical analysis was done using SPSS Version 20 Software. Result A total of 147 patients were included, 75.51% of whom experienced at least one drug therapy problem. During the 3 month period a total of 159 drug therapy problems were identified of which needs additional drug therapy (35.85%) was the most common followed by unnecessary drug therapy (30.19%) and dosage too low (13.2%). Antibiotics, 75 (40.32%) was the most frequent drug class involved in drug therapy problems followed by cardiovascular drugs, 69 (37.1%) and nonsteroidal anti-inflammatory drugs, 9 (4.84%). Ceftriaxone (25.81%) was the most frequent specific drug prone to the drug therapy problems followed by spiranolactone (14.52%), enalapril (6.45%) and furosemide (6.45%). Conclusions Three out of four patients experienced at least one drug therapy problem during their hospital stay in the medical ward, with the most commonly observed DTP being no drug therapy prescribed for a condition requiring drug treatment.